TRANSLATING ENGLISH -ED REDUCED RELATIVE CLAUSES INTO INDONESIAN: CORPUS EVIDENCE AND PEDAGOGICAL IMPLICATIONS - Sutrisno, Adi; Denistia, Karlina (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
The translation of reduced relative clauses from English to Indonesian is problematic because this construction exists in English but lacks a direct equivalent in Indonesian. This study investigates how -ed reduced relative clauses (RRCs) are realised in English and rendered into Indonesian by Google Translate, focusing on structural change, syntactic function, and modifier type. Using CQPWeb with the query “_NN +ed_VVN,” we extracted 285 sentences containing -ed RRCs from the Present-day English corpus. Results show that Indonesian translations consistently re-expand English RRCs into full clauses introduced by the obligatory relativiser yang, regardless of syntactic position (SS, OS, iOS, OPS, CS). This re-expansion preserves the syntactic role of the head noun but sometimes shifts modifier type due to lexical or predicate differences. These findings extend prior descriptions of Indonesian relativisation with corpus-based evidence from MT output and highlight typological constraints influencing how neural MT systems handle clause reduction. From the pedagogical perspective, the results highlight the need for explicit instruction on structural differences between English and Indonesian relative clauses, particularly the non-optional use of yang, in EFL learning. Integrating corpus-based MT examples into teaching could help learners process texts and improve translation accuracy.